Enhanced Fluorescent Siderophore Biosynthesis and Loss of Phenazine-1-Carboxamide in Phenotypic Variant of Pseudomonas chlororaphis HT66 - Liu, Yang; Wang, Zheng; Bilal, Muhammad; Hu, Hongbo; Wang, Wei; Huang, Xianqing; Peng, Huasong; Zhang, Xuehong (Frontiers in Microbiology, 2018)
Pseudomonas chlororaphis HT66 is a plant-beneficial bacterium that exhibits wider antagonistic spectrum against a variety of plant pathogenic fungi due to its main secondary metabolite, i.e., phenazine-1-carboxamide (PCN). In the present study, a spontaneous phenotypic variant designated as HT66-FLUO was isolated from the fermentation process of wild-type HT66 strain. The newly isolated phenotypic variant was morphologically distinct from the wild-type strain such as larger cell size, semi-transparent, non-production of PCN (Green or yellow crystals) and enhanced fluorescence under UV light. The whole-genome, RNA-sequencing, and phenotypic assays were performed to identify the reason of phenotypic variation in HT66-FLUO as compared to the HT66. Transcriptomic analysis revealed that 1,418 genes, representing approximately 22% of the 6393 open reading frames (ORFs) had undergone substantial reprogramming of gene expression in the HT66-FLUO. The whole-genome sequence indicated no gene alteration in HT66-FLUO as compared to HT66 according to the known reference sequence. The levels of global regulatory factor gacA and gacS expression were not significantly different between HT66 and HT66-FLUO. It was also observed that overexpressing gacS rather than gacA in HT66-FLUO can recover switching of the variant to HT66. The β-galactosidase (LacZ) activity and qRT-PCR results indicate the downregulated expression of rsmX, rsmY and rsmZ in HT66-FLUO as compared to HT66. Overexpressing three small RNAs in HT66-FLUO can revert switching of colony phenotype towards wild-type HT66 up to a certain degree, restore partial PCN production and reduces the fluorescent siderophores yield. However, the origin of the spontaneous phenotypic variant was difficult to be determined. In conclusion, this study helps to understand the gene regulatory effect in the spontaneous phenotypic variant.